Enhanced osseous integration of human trabecular allografts following surface modification with bioactive lipids - Wang, Tiffany (Drug Deliv Transl Res, 2016)
In this study, we used extracellular matrix (ECM) gels and human bone allograft as matrix vehicles to deliver the sphingolipid growth factor FTY720 to rodent models of tibial fracture and a critical-sized cranial defect. We show that FTY720 released from injectable ECM gels may accelerate callous formation and resolution and bone volume in a mouse tibial fracture model. We then show that FTY720 binds directly to human trabecular allograft bone and releases over 1 week in vitro. Rat critical-sized cranial defects treated with FTY720-coated grafts show increases in vascularization and bone deposition, with histological and micro-computed topography (microCT) evidence of enhanced bone formation within the graft and defect void. Immunohistochemical analysis suggests that osteogenesis within FTY720-coated grafts is associated with reduced CD68(+) macrophage infiltration and recruitment of CD29(+) bone progenitor cells. Matrix binding of FTY720 thus represents a promising and robust bone regeneration strategy with potential clinical translatability.